Dual Implantation of Artificial Urinary Sphincter and Inflatable Penile Prostheses for Concurrent Male Urinary Incontinence and Erectile Dysfunction - Tariq F. Al-Shaiji (Advances in Urology)
Erectile dysfunction and urinary incontinence secondary to sphincter dysfunction are common conditions affecting many men worldwide with a negative effect on quality of life. They are encountered in a number of etiologies most commonly following radical prostatectomy in which they coexist in the same patient. Implantations of an artificial urinary sphincter and inflatable penile prosthesis have proven to be effective in the treatment of both conditions should conservative and minimally invasive measures fail. The recent literature has shown that dual implantation of these devices is feasible and safe with a durable clinical outcome. Once indicated, this can be done in a synchronous or nonsynchronous manner; however, the emerging of the single transverse scrotal incision as well as advancement in the prostheses has made synchronous dual implantation more favourable and appealing option. It provides time and cost savings with an evidence of high patient satisfaction. Synchronous dual implantation should be offered initially when indicated. This paper discusses the surgical techniques of artificial urinary sphincter and inflatable penile prosthesis dual implantation in the management of concurrent moderate-to-severe urinary incontinence and medically refractive erectile dysfunction, in addition to highlighting the existing literature pertaining to this approach.